2006
DOI: 10.1111/j.1469-7998.2006.00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection and habitat‐specific survival of fledgling ovenbirds (Seiurus aurocapilla)

Abstract: Patterns of habitat use by some passerines change after the young leave the nest, and thus our understanding of habitat selection derived from counts of singing males earlier in the nesting cycle may not adequately represent the breeding habitat requirements of these species. Post-fledging changes in habitat use may have important conservation implications if the survival of fledglings is affected by characteristics of the habitat; however, there have been relatively few systematic studies of the post-fledging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
105
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 34 publications
9
105
2
Order By: Relevance
“…Dixon 1972;Anders et al 1997;Cohen & Lindell 2004;King et al 2006;Rivers et al 2012), I did not find evidence that corticosterone-treated birds had higher survival rates during the pre-migratory period compared to sham or controls. One explanation may be the lack of power due to the low number of recaptures.…”
mentioning
confidence: 90%
“…Dixon 1972;Anders et al 1997;Cohen & Lindell 2004;King et al 2006;Rivers et al 2012), I did not find evidence that corticosterone-treated birds had higher survival rates during the pre-migratory period compared to sham or controls. One explanation may be the lack of power due to the low number of recaptures.…”
mentioning
confidence: 90%
“…Juvenile Swainson's Thrush (Catharus ustulatus) move from riparian areas to mixed-hardwood forests and coastal scrub after fledging, searching for ripening fruit (White et al 2005). Recent netting studies within clearcuts in eastern deciduous forest have expanded the list of forest-breeding species that appear to use second-growth vegetation in late summer, but these studies did not show if such habitats were required by these species (Marshall et al 2003, King et al 2006, Vitz and Rodewald 2006; J. Faaborg, P. A. Porneluzi, R. Brito-Aguilar, and R. L. Clawson, unpublished manuscript). These post-breeding habitats may be critical to both the juvenile and adult survival components of breeding-season fitness, but they have not been studied in depth (Ahlering andFaaborg 2006, Whittaker andMarzluff 2009).…”
Section: Habitat Selection and Suitabilitymentioning
confidence: 99%
“…Common explanations given for high bird use in young regenerating stands during these two critical time periods are increased areas of cover and/or high insect and fruit abundance associated with these areas (Anders et al 1998, King et al 2006, McDermott and Wood 2010, Rodewald and Brittingham 2004, Vitz and Rodewald 2007. Additionally, Stoleson (2010) found that capture rates increased almost linearly with increasing clearcut size, suggesting that larger cuts may provide a greater benefit.…”
Section: E F Discussion and Management Implicationsmentioning
confidence: 99%